Sustained therapeutic effects of percutaneous tibial nerve stimulation: 24‐month results of the STEP study123. Issue 1 (5th June 2012) - Peters, Kenneth M.; Carrico, Donna J.; MacDiarmid, Scott A.; Wooldridge, Leslie S.; Khan, Ansar U.; McCoy, Craig E.; Franco, Nicholas; Bennett, Jason B.
Abstract Aims To evaluate the safety, sustained effectiveness, and treatment interval for percutaneous tibial nerve stimulation (PTNS) for overactive bladder (OAB) therapy through 24 months. Methods A prospective study following treatment success after 12 weekly PTNS treatments, subjects were prescribed a 14‐week tapering protocol, followed by ongoing therapy with a Personal Treatment Plan determined by the investigator and subject to sustain subject OAB symptom improvement. Questionnaires were completed every 3 months, voiding diaries every 6 months; adverse events were reported throughout. Results Of 50 subjects enrolled, 35 remained in the study at 24 months. During the 24 months following initial treatment success and a 14‐week tapering protocol, mean treatments per month was 1.3. Voiding diary and OAB‐q data demonstrate sustained improvement reported at 13 weeks through 24 months. Improvements in frequency, urge incontinence episodes, night‐time voids and moderate‐to‐severe urgency episodes from voiding diaries at 6, 12, 18, and 24 months were statistically significant compared to baseline (prior to initial 12 weekly treatments). Compared to baseline, OAB‐q symptom severity scores and health related quality of life scores were statistically significant for improvement at each tested time point. Five mild adverse events of unknown relation to treatment were reported. Conclusion Sustained safety and efficacy of PTNS were demonstrated over 24 months with initial success after 12 weekly treatments, followed by a 14‐week prescribed tapering protocol and a Personalized Treatment Plan. With an average of 1.3 treatments per month, PTNS therapy is a safe, durable, and valuable long‐term OAB treatment option to sustain clinically significant OAB symptom control. Neurourol. Urodynam. 32: 24–29, 2013. © 2012 Wiley Periodicals, Inc.